2003
DOI: 10.1046/j.1365-2656.2003.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient exchanges between marine and terrestrial ecosystems: the case of the Galapagos sea lion Zalophus wollebaecki

Abstract: Summary1. The movement of materials and organisms between ecosystems is a common process in nature. 2. In the present study we investigate the hypothesis that the transport of nutrients by low-mobility species and their effect on terrestrial ecosystems depends on habitat topography. Specifically, we hypothesized that the influence of a marine organism with low mobility on terrestrial environments would be spatially restricted. 3. To address this hypothesis we analysed the distribution (both geographical and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 60 publications
0
51
0
Order By: Relevance
“…Galapagos fur seal ); Antarctic fur seal (Costa et al 2001); South American fur seal ); subantarctic fur seal (Geprges et al 2000b); cape fur seal ); Au'stralian fur seal (Arnauld and Hindell 2001); Galapagos sea lion ); Australian sea lion (Costa and Gales 2003); California sea lion (Feldkamp et al 1989); New Zealand sea lion (Costa and Gales 2000); Southern sea lion (Thompson et al 1998). ' feeds exclusively within Bass Strait between the Australian mainland and Tasmania, an area considered nutrient-poor with low marine productivity (Warneke and Shaughnessy 1985), Similarly, California sea lions on the California coast are epipelagic foragers in the cold productive waters of the California Current (Feldkamp et al 1989(Feldkamp et al , 1991, whereas the continental shelf habitat of the benthic foraging Galapagos sea lion is of generally low~r productivity (Farina et al 2003, Okey et al 2004. [t may be that, exc"ept in very productive regions, large size precludes foraging on .…”
Section: Discussionmentioning
confidence: 99%
“…Galapagos fur seal ); Antarctic fur seal (Costa et al 2001); South American fur seal ); subantarctic fur seal (Geprges et al 2000b); cape fur seal ); Au'stralian fur seal (Arnauld and Hindell 2001); Galapagos sea lion ); Australian sea lion (Costa and Gales 2003); California sea lion (Feldkamp et al 1989); New Zealand sea lion (Costa and Gales 2000); Southern sea lion (Thompson et al 1998). ' feeds exclusively within Bass Strait between the Australian mainland and Tasmania, an area considered nutrient-poor with low marine productivity (Warneke and Shaughnessy 1985), Similarly, California sea lions on the California coast are epipelagic foragers in the cold productive waters of the California Current (Feldkamp et al 1989(Feldkamp et al , 1991, whereas the continental shelf habitat of the benthic foraging Galapagos sea lion is of generally low~r productivity (Farina et al 2003, Okey et al 2004. [t may be that, exc"ept in very productive regions, large size precludes foraging on .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the nutrient elements such as N and P are important limiting factors for aquatic plants in oligotrophic Antarctic and Arctic lakes, and allochthonous inputs into lake water may cause eutrophication and thus the increase of phytoplankton biomass (Hawes 1983;Blais et al 2005;Keatley et al 2009;Michelutti, Blais, Cumming et al 2010). Nutrient transport by migratory animals generally plays an important role in the development of ecosystems (Anderson & Polis 1999;Fariñ a et al 2003;Blais et al 2007;Hannan et al 2007). The nutrient subsidies derived from animal excrements can impact the ecosystem structure and function, particularly in remote islands (Polis et al 1997;Michelutti et al 2008).…”
Section: Effect Of Seabird Droppings Input On East Antarctic Lake Primentioning
confidence: 99%
“…Further, Zalophus wollebaeki provide an important ecosystem function as transporters of marine nutrients to terrestrial habitats of the Galapagos Islands (Fariña et al 2003). Despite their vulnerability (Seal Specialist Group 1996) and importance, very little is known about the marine habitat utilization of these sea lions.…”
Section: Introductionmentioning
confidence: 99%
“…Births occur from June to March, but the peak pupping period varies among rookeries and years. Pups are weaned at a time when they are independently foraging -usually around 2 to 3 yr old (Trillmich 1986, Heath 2002.Prey species found in the diet of Zalophus wollebaeki from multiple colonies include epipelagic fish (Clupeidae) of surface and coastal upwelling waters, mesopelagic fish (Myctophidae) found in deep waters of the open ocean, and demersal, benthopelagic or pelagic fish (Chlorophtalmidae, Serranidae and Mugilidae) found over muddy and sandy bottoms of the continental shelf or in shallow and deep waters between rocks (Salazar 2005, Froese & Pauly 2006.Further, Zalophus wollebaeki provide an important ecosystem function as transporters of marine nutrients to terrestrial habitats of the Galapagos Islands (Fariña et al 2003). Despite their vulnerability (Seal Specialist Group 1996) and importance, very little is known about the marine habitat utilization of these sea lions.…”
mentioning
confidence: 99%